Psychosocial risks in intensive care nursing: reflection on possible solutions - Jorge Luiz Lima da Silva; Gilvania Barreto Feitosa Coutinho; Eliana Napoleão Cozendey da Silva; Liliane Reis Teixeira; Karine Barreto Rodrigues da Silva; Rafael da Silva Soares (Universidade Federal de Santa Maria, 2017)
Aim: Discussing stress, burnout and possible solutions for coping with the nursing professional working in intensive care units. Method: this was a reflexive study. Results: it was noticed that the work stress comes from three main axes, the ICU setting, the work process in the environment in question and also the stress inherent in the activity itself of the nursing professional. From these issues, these factors were grouped into institutional, political and quality of life in the workplace, to elucidate. Conclusion: collective effort, political conditions and institutional aspects are necessary to improve the worker's quality of life. Individual resilience and coping are insufficient when the work environment is not adequate.